Платон и системот на динамичка онтологија - Solunchev, Risto (Филозофски факултет, Скопје, 2016)
The aim of the author is to examine the relation between the synthetic system of ontology of St. Maximus the Confessor and the concept of being in Plato’s philosophy. Namely, St. Maximus is not a neoplatonic thinker influenced by Neo-platonic philosophical paradigm, but is, in its core, influenced by the Plato and its Timaeus. The claim of Plato that the real being is transcendent in itself, and that there is an ontological discrepancy between that being and this world are the main postulates of St. Maximus’ system. The key issue for Plato, as well as for St. Maximus, is to keep this ontological heterogeneity, but, in the same time, to resolve the problem of participation of the real being into this world and vice versa. Plotinus and Neoplatonism resolve the problem by asserting that the world is one causal effect, an ennead from the One, abolishing the ontological discrepancy in a pantheistic manner. After Plato, only one bifurcation is possible, directing the ontology to Plotin on one side, and to christian philosophy on other side. The complex system of St. Maximus the Confessor’s ontology of logoi set in the world (ontology based on difference between the essence of God and God’s uncreated energies which are intentions of God’s extatical love that participate in his creation), resolves the problem of Plato: how to keep the source of being as transcendent essence, and in the same time to save the world ontology not as a shadow but as eikona, as a symbol, as a part of the life of God’s Logos - Christ.
Plato and the System of Dynamic Ontology